QUACQUERELLI SYMONDS ASIA UNIVERSITY RANKINGS USING COBIT 5 FRAMEWORK - Iwan Rijayana; Mohd Haizam Saudi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Telkom University is one of the most private colleges in Bandung, which has participated in national and International University rankings. One of the international rankings followed by Telkom Universities is the rating of QS (Quacquarelli Symonds) Top Universities. QS is a leading global career and education network for ambitious professionals who want to develop their personal and professional development. Some of the indicators required for inputting are academic reputation, employee reputation, and number of domestic and international students, citation of scientific work, international research Network and several other indicators. To be able to follow QSAUR (QSAsia University Rankings), the university is required to be able to complete the data divided into several indicators. Some of these indicators are academic reputation, employee reputation, number of domestic and international students, citation of scientific work, international research Network and several other indicators. The amount of data and the number of indicators did not slightly make the University of Telkom decided to create an information system that can be used to support and manage the data needed for QS. It was built an information system called Dashboard QS AUR. To be able to assess the quality of the information system that the Dashboard QSAUR, it takes an audit process information system to increase the value of capability. Information system audits are implemented to be able to know the future development recommendations for the QS AUR Dashboard Information System. The method used is COBIT 5 that focuses on the Align, Plan, and Organize (APO) domains of the domain APO 01 upto APO13 and its sub-domains. Overall the result achieved for the QSAUR information system is level 4 (predictable process) which means that most of the activities are already done and have predictions for the future. Once obtained the capability value, proceed by providing recommendations for the future.